17 A case-control study with computational modelling of acute left ventricular dysfunction. (18th April 2016) - Gao, H; Mangion, K; Carrick, D; Luo, X; Berry, C
Abstract : Introduction: The pathophysiology of acute left ventricular dysfunction after acute ST-elevation myocardial infarction (STEMI) is incompletely understood. In this study, we carried out a case-control study of left ventricular (LV) biomechanical behaviour in vivo using an immersed boundary-finite element (IB/FE) method. Methods: Cardiac magnetic resonance images were acquired from six healthy volunteers (the healthy group) and six patients with acute LV dysfunction post-acute STEMI (the MI group) with no-reflow, defined as an acute reduction in myocardial blood flow despite a patent epicardial coronary artery. The two groups were age matched. The passive and active myocardial parameters were determined from the measured in vivo data (LV cavity volume and strain) to match the LV dynamics in diastole and systole. Results: Student's t-test was used for significance test. Our results show that even though the average measured peak cuff-pressure in the MI group is much lower than the healthy group (122 ± 21 vs. 150 ± 20mmHg, p < 0.05), the peak systolic active tension in the MI group is higher (68.9 ± 6.8 vs. 64.7 ± 8.4kPa, p = 0.15), therefore the required active tension per mmHg increase is significantly higher in the MI group (0.57 ± 0.05 vs. 0.43 ± 0.05 kPa/mmHg, p < 0.01), which may suggest that the viable myocardium in the MI group is working harder to compensate for the loss of contraction even with much lower blood pressure. Compared to the healthy group, the MI group also has a larger end-diastolic volume (143 ± 23 vs. 122 ± 16 mL, p = 0.09), and a lower ejection fraction (39 ± 3% vs. 53 ± 2%, p < 0.01). Conclusions: In summary, we have shown for the first time that, compared with controls, patients with recent ST-elevation myocardial infarction exhibit increased active tension generation in combination with predictable changes in end-diastolic volume and ejection fraction. Active tension generation is a novel biomechanical index, and its clinical and prognostic significance merits further study. Funding: British Heart Foundation (PG/14/64/31043)